The Potential of Nutmeg’s Microbes (Myristica fragrans Houtt.) as Antagonistic Agents against Rigidoporus microporus - Dwi N Susilowati; Sri Rahayuningsih; Indah Sofiana; Nani Radiastuti (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
This study aimed to obtain yeast and bacteria from Myristica fragrans Houtt., which have the potential to produce chitinase enzymes with antagonistic ability against Rigidoporus microporous. Both microorganisms were extracted from the leaves and fruit of nutmeg. A total of 35 yeast and 29 bacterial isolates were obtained, with different morphological characters. The chitinolytic test was carried out qualitatively, and the parameters observed include the clear zones around the colony. A total of 4 bacterial isolates produced chitinase enzymes (BP 1.2.1, BP 2.1.1, EPBj II.K1, and EPBj II. K2) with a chitinolytic index of 3.92, 5.38, 2.00, and 1.66, respectively. Yeast isolates were negative for chitinase enzymes. The difference in index value indicated a variation in enzyme activity. The antagonist test was carried out using a dual culture method. A total of 1 yeast and 14 bacterial isolates inhibited the growth of R. microporous, and each has a different inhibitory zone. Based on the percentage of inhibition value, the highest percentage occurred in P.K1(41.1%), P. K2 (50%), dan EPBj II. K6 (42.2%). The antagonist test indicator includes the formation of inhibitory zones on the medium. Hemolysis test showed that yeast and bacteria are not able to break down blood cells in the medium. The molecular identification showed that P. K1 and P. K2 isolates were classified as Bacillus subtillis and EPBj II. K6 were identified as Bacillus aerius with 100% sequence homology and 99% bootstrap value respectively. These findings provided information about potential microbes that control white root fungus.